2017
DOI: 10.1080/09168451.2016.1238297
|View full text |Cite
|
Sign up to set email alerts
|

High production of a class III lantipeptide AmfS in Streptomyces griseus

Abstract: AmfS, a class III lantipeptide serves as a morphogen in Streptomyces griseus. Here, we constructed a high production system of AmfS in S. griseus. We isolated S. griseus Grd1 strain defective in glucose repression of aerial mycelium formation and found it suitable for the overproduction of AmfS. Two expression vectors carrying the strong and constitutive ermE2 promoter were constructed using a multicopy number plasmid, pIJ702. The use of the Grd1 strain combined with the expression vectors enabled high product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Several other peptides with sequence homology to SapB have been identified including AmfS ( 36 ), produced in Streptomyces griseus (Figure ). , AmfS is also important for aerial hyphae formation and sporulation. , Mutagenesis studies of AmfS revealed that all conserved post-translationally modified residues selected for replacement (Ser3, Cys10, Ser13, Ser16, and Cys20) were essential for activity . Ser6, although conserved and converted to Dha, was not targeted by mutagenesis in this study.…”
Section: Lanthipeptides and Compounds Made Via Related Pathwaysmentioning
confidence: 99%
“…Several other peptides with sequence homology to SapB have been identified including AmfS ( 36 ), produced in Streptomyces griseus (Figure ). , AmfS is also important for aerial hyphae formation and sporulation. , Mutagenesis studies of AmfS revealed that all conserved post-translationally modified residues selected for replacement (Ser3, Cys10, Ser13, Ser16, and Cys20) were essential for activity . Ser6, although conserved and converted to Dha, was not targeted by mutagenesis in this study.…”
Section: Lanthipeptides and Compounds Made Via Related Pathwaysmentioning
confidence: 99%
“…The remaining 21 compounds that were not detected by dereplication were mainly classified as siderophores, terpenes, lanthipeptides, lasso peptides, lipopeptides, ectoine, butyrolactone and melanin. Our inability to detect these compounds could be due to two different reasons: (i) they were not being produced under our laboratory conditions or (ii) the extraction method using ethyl acetate is not suitable for this type of metabolites, and other solvents (e.g., n-butanol or ethanol) should be used instead [49][50][51][52].…”
Section: Correlation Between Bgcs Detected By Antismash Analysis and Dereplication Resultsmentioning
confidence: 99%
“…2A). The ermE * promoter is one of the most widely used promoters for heterologous gene expression in streptomycetes (Lombó et al ., 2006; Park et al ., 2009; Wang et al ., 2012; Takano et al ., 2017; Liu et al ., 2018), and its correct activity for controlling flavonoid biosynthetic genes has been confirmed in previous studies of this research group (Marín et al ., 2017, 2018; García‐Gutiérrez et al ., 2020). Genes were selected from different bacteria ( Rhodobacter capsulatus and S. coelicolor ) and plants ( Glycine max, Petroselinum crispum and Arabidopsis thaliana ) as they were already tested in the laboratory for these enzymatic steps (Marín et al ., 2017, 2018; García‐Gutiérrez et al ., 2020).…”
Section: Resultsmentioning
confidence: 99%